2009
DOI: 10.1111/j.1462-2920.2009.01908.x
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic adjustment and requirement for sodium in marine protist thraustochytrid

Abstract: A non-invasive ion-selective microelectrode technique was used to elucidate the ionic mechanisms of osmotic adjustment in a marine protist thraustochytrid. Hypoosmotic stress caused significant efflux of Na + , Cl -and K + from thraustochytrid cells. Model calculations showed that almost complete osmotic adjustment was achieved within the first 30 min after stress onset. Of these, sodium was the major contributor (more than half of the total osmotic adjustment), with chloride being the second major contributor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…Based on this, the inhibition of turgor recovery in our experiments could be due to the inhibition of Na + uptake through NSCC, considering that Na + uptake was shown to be the major contributor to cell turgor in a marine species of the stramenopile, Thraustochytrium (Shabala et al. ).…”
Section: Discussionmentioning
confidence: 73%
“…Based on this, the inhibition of turgor recovery in our experiments could be due to the inhibition of Na + uptake through NSCC, considering that Na + uptake was shown to be the major contributor to cell turgor in a marine species of the stramenopile, Thraustochytrium (Shabala et al. ).…”
Section: Discussionmentioning
confidence: 73%
“…In addition, salt stress generated an increase in reactive oxygen species (ROS), which leaded to decreases in plant photosynthetic capacity [38]. Despite the absence of data of salt stress effects on leaf photochemistry in this study, the fact that NaCl treatment caused a very significant reduction in net CO 2 assimilation, being closely correlated with biomass and plant height, has been proven [39]. Therefore, it appeared that stomatal limitation of photosynthesis was an important factor reducing halophytes growth in saline conditions.…”
Section: Discussionmentioning
confidence: 86%
“…As far as cell lines are concerned, previous study showed that the maintenance of PEG-resistant cell line on a medium completely free of Na induced a PEG-sensitive phenotype, while an exogenous application of Na increased the ability of PEG-sensitive cell line to cope with water stress (Martínez et al, 2005). Sodium was recently shown to play a key role in osmotic adjustment in some lower marine fungi (Shabala et al, 2009) but such a function is unlikely in our cell lines since exogenous NaCl induces only a small decrease inCs (despite a strong increase in endogenous Na) comparatively to Cd in the absence of NaCl (which only slightly increased endogenous Na) (Tables 1 and 2). Small amounts of Na are required for efficient photosynthesis in C4 plant species, mainly in relation to phosphoenolpyruvate regeneration, but this should not be considered in our heterotrophic cell lines maintained in dark conditions and further works are thus required to identify the specific functions of Na in A. halimus.…”
Section: Discussionmentioning
confidence: 99%